(untitled) (IJM: Journal of Multidisiplinary, 2025)
Occupational Health and Safety (OHS) risk management is a vital component in ensuring worker safety and smooth operational flow in infrastructure projects, particularly in the toll road transportation sector, which involves a high level of potential hazards. This study aims to thoroughly analyze the impact of OHS risk management implementation on the performance of toll road construction and operations, with a focus on risk identification, hazard assessment, and control strategies applied in the field. The research method used is a literature review, collecting and evaluating data from various scientific journals, technical reports, and previous studies relevant to the topic. The findings indicate that a systematic and continuous implementation of OHS risk management significantly reduces workplace accidents, enhances worker productivity, and prevents project delays caused by safety-related disruptions. Furthermore, the integration of OHS aspects into every phase of the project from planning to operations contributes to the development of a disciplined, risk-aware, and responsible work culture. OHS risk management serves not only as a tool for hazard control but also as a key driver for achieving optimal, efficient, and sustainable performance in toll road projects over the long term.